Association between inflammatory bowel disease and pancreatic cancer: results from the two-sample Mendelian randomization study - Min, Yu; Liu, Zheran; Li, Ruidan; Jin, Jing; Wei, Zhigong; Pei, Yiyan; Hu, Xiaolin; Peng, Xingchen (Frontiers in Oncology, 2023)
Background The nuanced relationship between inflammatory bowel disease (IBD) and pancreatic cancer is noticed in recent years. However, the underlying causal effects of these two diseases are still unclear. Methods The two-sample mendelian randomization (MR) was conducted to explore the causal effect of IBD condition on pancreatic cancer. Methods of Wald ratio, inverse variance weighted (IVW), MR-Egger, weighted median, and weighted mode were used to investigate the causal relationship between IBD and pancreatic cancer. Besides, Cochrane’s Q test, MR-Egger, and leave-one-out method were further conducted to detect heterogeneity, stability, and pleiotropy of MR results. Results In the MR analysis, we found Crohn’s disease had a significant causal effect on pancreatic cancer. Specifically, Crohn’s disease would increase 11.1% the risk of pancreatic cancer by the IVW method (p= 0.022), 33.8% by MR Egger (p= 0.015), by 35.3% by the Weighted model (p= 0.005). Regarding ulcerative colitis, there was no statistically significant causal effect observed on pancreatic cancer (p>0.05). Additionally, the pleiotropic test and Leave-one-out analysis both proved the validity and reliability of the present two-sample MR analyses. Conclusion This study indicates that IBD, particularly Crohn’s disease, is causality associated with increased risk of pancreatic cancer. Our results may help public health managers to make better follow-up surveillance of IBD patients.